Réponses

  • Utilisateur Brainly
2013-11-15T21:43:36+01:00
(tg²43°- sin²43°) / (cotg47° + cos47°)
=(sin(43°)/cos(43°)-sin(43°))/(cos(47°)/sin(47°)+cos(47°))

=(sin(43°)/cos(43°)-sin(43°))/(sin(43°)/cos(43°)+sin(43°))
=(sin(43°)-sin(43°)*cos(43°))/(sin(43°)+sin(43°)*cos(43°))
=(1-cos(43°))/(1+cos(43°))
=(1-cos(43°))²/(1-cos²(43°))
=(1-2cos(43°)+cos²(43°))/sin²(43°)
=sin(86°)/sin²(43°)+cos²(43°)/sin²(43°)
=sin(43°)/cos(43°)-sin(43°)
=tg(43°)-sin(43°)
= tg(43°) - cos(47°)


je ne comprends pas l'etape ou vous etes passer a 1-cos(43°) pouvez vous m'expliquer ?